Epidermoid cyst of the buccal mucosa—An uncommon entity: Case report and literature review. Issue 9 (21st September 2021) - Dammak, Nouha; Chokri, Abdellatif; Slim, Afef; Bellalah, Ahlem; Bouguezzi, Adel; Sioud, Sameh; Hentati, Hajer; Selmi, Jamil
Abstract: Epidermoid cyst of the buccal mucosa is rare. Nevertheless, it must be included in the differential diagnosis of swelling in this area. The diagnosis is based on anatomopathological examination. The surgical enucleation is the gold standard of treatment. Abstract : Epidermoid cyst of the buccal mucosa is rare. Nevertheless, it must be included in the differential diagnosis of swelling in this area. The diagnosis is based on anatomopathological examination. The surgical enucleation is the gold standard of treatment.